Multiplexed LC–ESI–MRM‐MS‐based Assay for Identification of Coronary Artery Disease Biomarkers in Human Plasma - Anwar, Mohammad A.; Dai, Darlene Liying; Wilson‐McManus, Janet; Smith, Derek; Francis, Gordon A.; Borchers, Christoph H; McManus, Bruce M.; Hill, John S.; Cohen Freue, Gabriela V. (Proteomics. Clinical applications, 2019)
Purpose A highly‐multiplexed LC–ESI–multiple reaction monitoring‐MS‐based assay is developed for the identification of coronary artery disease (CAD) biomarkers in human plasma. Experimental design The assay is used to measure 107 stable isotope labeled peptide standards and native peptides from 64 putative biomarkers of cardiovascular diseases in tryptic digests of plasma from subjects with (n = 70) and without (n = 45) angiographic evidence of CAD and no subsequent cardiovascular mortality during follow‐up. Results Extensive computational and statistical analysis reveals six plasma proteins associated with CAD, namely apolipoprotein CII, C reactive protein, CD5 antigen‐like, fibronectin, inter alpha trypsin inhibitor heavy chain H1, and protein S. The identified proteins are combined into a LASSO‐logistic score with high classification performance (cross‐validated area under the curve = 0.74). When combined with a separate score computed from markers currently used in the clinic with similar performance, the area under the receiver operating curve increases to 0.84. Similar results are observed in an independent set of subjects (n = 87). Conclusions and clinical relevance If externally validated, the assay and identified biomarkers can improve CAD risk stratification.